1996
DOI: 10.1128/jvi.70.4.2545-2555.1996
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Epstein-Barr virus DNA polymerase promoter by the BRLF1 immediate-early protein is mediated through USF and E2F

Abstract: The Epstein-Barr virus (EBV) DNA polymerase (pol) is essential for the replication of viral genomes during productive EBV infection. We have previously reported that the EBV DNA pol promoter, which is TATA-less and constitutively inactive, is activated by a genomic clone expressing both immediate-early viral transactivators, BZLF1Z and BRLF1 (R), in EBV-infected lymphoid cells. Here we demonstrate that R alone is sufficient to activate the pol promoter in EBV-negative B cells. Unlike other early promoters to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 93 publications
(119 reference statements)
0
25
0
Order By: Relevance
“…Nevertheless, the consistent pattern of results obtained from different patients with different HLA backgrounds, added to more limited data from an earlier study (18), suggests that the hierarchy of immunodominance observed is indeed real. The relationship between immunodominance and time of antigen expression in the lytic cycle is further emphasized by the fact that, of the four most commonly recognized antigens within the E protein group, BMLF1 and BMRF1 are proteins whose synthesis is directly induced by the BZLF1 and BRLF1 IE transactivators (24)(25)(26)(27), whereas BALF5, and potentially also BALF2, synthesis is induced by BRLF1 acting in concert with cellular transcription factors (28). Therefore, the expression of such proteins would be among the first markers of progression into early phase.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the consistent pattern of results obtained from different patients with different HLA backgrounds, added to more limited data from an earlier study (18), suggests that the hierarchy of immunodominance observed is indeed real. The relationship between immunodominance and time of antigen expression in the lytic cycle is further emphasized by the fact that, of the four most commonly recognized antigens within the E protein group, BMLF1 and BMRF1 are proteins whose synthesis is directly induced by the BZLF1 and BRLF1 IE transactivators (24)(25)(26)(27), whereas BALF5, and potentially also BALF2, synthesis is induced by BRLF1 acting in concert with cellular transcription factors (28). Therefore, the expression of such proteins would be among the first markers of progression into early phase.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from our laboratory suggested that Rb may be a target for the R protein. R activation of the promoter for the EBV pol gene has been mapped to elements which bind the transcription factors USF and E2F; mutation at either site reduced R-mediated activation of pol (42). Additional promoters are activated by R in an indirect manner (26,52,57,82).…”
Section: Discussionmentioning
confidence: 99%
“…The 605-amino-acid (aa) R protein contains two transactivation domains and an N-terminal DNA-binding and dimerization domain (29,44). R can activate promoters both by binding a specific DNA sequence, an R-responsive element (29,44), and indirectly, possibly by activating or recruiting cellular transcription factors (42,81,82). Promoters activated in the latter manner include BRLF1 itself (57,82), the human immunodeficiency virus long terminal repeat (52), and c-myc (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…De-regulation of the mammalian cell cycle Q 2001 Blackwell Science Ltd, International Journal of Experimental Pathology, 82, 3±13 through transcription factors USF and E2F (Liu et al 1996). EBNALP is also reported to interact with Rb in vitro and localize with Rb in the cell (Szekely et al 1993).…”
Section: Viruses and Cancermentioning
confidence: 99%